A Sphingomyelin-Sensing Pathway Governing Metabolic Inflammation - Zheng, Jianfei; Xu, Chunling; Wang, Zhuo; Yao, Tao; Wang, Haodong; Lin, Xubo; Zhu, Kangling; Liu, Yurong; Peng, Dong; Chen, Fengwu; Qin, Zhewen; Zhang, Min; et al. (浪淘沙预印本平台, 2026)
Obesity-associated metabolic inflammation is driven by lipid-laden macrophages that release proinflammatory cytokines such as interleukin-1β, yet how macrophages sense lipid overload to trigger inflammation remains unclear. Here, we identify sphingomyelin sensing as a key mechanism linking lipid metabolism to inflammatory activation. We show that macrophages detect specific sphingomyelin species to induce metabolic inflammation through the TMED10-channeled unconventional secretion (THU) pathway, a recently discovered non-lytic route for cytokine release distinct from GSDMD-dependent pyroptosis. Single-cell transcriptomic profiling revealed a metabolic inflammation macrophage subset with enhanced lipid uptake, active sphingomyelin metabolism, and elevated TMED10 expression, marking a population tuned to metabolic stress and inflammation. A high-fat diet feeding induced a shift toward medium-chain sphingomyelin species in the adipose tissue macrophages, which potently activated TMED10 and promoted IL-1β secretion via the THU pathway. TMED10 directly binds sphingomyelin through its transmembrane domain, with residue Q204 being essential for this interaction. TMED10 displays high sensitivity to medium-chain sphingomyelin (EC50 ≈ 0.5%), underscoring its role as a precise lipid sensor. Mutation of Q204 disrupted sphingomyelin binding, impaired IL-1β release, and protected mice from metabolic inflammation. Together, these findings establish a TMED10-sphingomyelin axis as a molecular circuit that senses lipid composition to drive chronic inflammation, revealing new therapeutic opportunities for obesity and other lipid-associated inflammatory disorders.